Land use dynamics and the status of soil fertility under different land uses in the Embamamie watershed, Northwest Ethiopia: land use change and soil fertility - Meles, Zenaw; Molla, Eyayu (Ethiopian Journal of Social Sciences, 2024)
Land degradation and a decline in soil fertility are caused by land use changes and improper land management practices. This study analyzed land use and cover change from 1990–2021 and evaluated the effects of different land uses on soil fertility in the Embamamie watershed, northwest Ethiopia. ERDAS Imagine 2015 and Arc GIS 10.7 software were used to analyze satellite images. Four land use types – natural forest, plantation forest, cultivated land, and grazing land were selected to evaluate changes in soil fertility under different land uses. Soil samples were collected at depths of 0–20 and 20–40 cm and analyzed following the standard soil analytical procedures. The study found that natural forest and grazing land declined by 8.80% and 20.07%, respectively, while cultivated land and settlement areas increased by 25.63 and 3.24%, respectively, in the watershed. Soil analysis revealed that natural forests had the highest percentages of clay, silt, moisture content, porosity, pH, organic carbon, total nitrogen, available phosphorus, cation exchange capacity, and exchangeable bases, whereas cultivated land had the highest sand fraction and bulk density. These changes were the result of population pressure that demanded more land for cultivation and settlement areas. The disturbance of the ecosystem brought about by improper land use and management resulted in the decline of natural forests and a loss in soil fertility, particularly in cultivated land. The study suggests that immediate intervention with appropriate land use and management practices is needed to conserve and rehabilitate the natural forests and degraded soil for sustainable agricultural productivity.